Cutting, Interruption, and the End of Hamlet. (30th June 2016) - Dobson, Michael
Abstract : In this essay Michael Dobson considers the evolution of certain habitual cuts to the text of Hamlet between the seventeenth and early twentieth centuries, identifying in particular a tendency to increase the abruptness with which the play's last act interrupts its otherwise digressive movement. Looking in particular at the fate of Fortinbras, he examines changes to the ways in which these cuts have been indicated to readers, arguing that a decisive separation between the play as read and as acted makes itself felt at the turn of the nineteenth century. He concludes with a discussion of when and why it became desirable to advertise not manageably edited stage versions, but 'uncut' marathons. Michael Dobson is Director of the Shakespeare Institute in Stratford-upon-Avon and Professor of Shakespeare Studies at the University of Birmingham. His publications include the co-editorship of The Oxford Companion to Shakespeare, Shakespeare and Amateur Performance, Performing Shakespeare's Tragedies Today, and The Making of the National Poet .